Multitarget CDK inhibitors roscovitine and UCN‑01 induce apoptosis in colorectal cancer cells by inhibiting cell cycle progression and transcription - Sonal Mohan Manohar; Kalpana Sanjay Joshi (Brazilian Journal of Pharmaceutical Sciences)
Abstract Colorectal cancer (CRC) is the third leading cause of cancer death in the world, and its incidence is steadily rising in developing nations. Cell cycle aberrations due to deregulation of cyclin dependent kinases (CDKs) and cyclins are common events during colorectal carcinogenesis. Herein, we investigate the anticancer potential of two multitarget CDK inhibitors viz. roscovitine (specific inhibitor of CDK1, 2, 7, and 9) and UCN-01 (pan CDK inhibitor) against three CRC cell lines. Both the drugs exerted cytotoxicity and inhibited clonogenic potential of human CRC cell lines. These drugs induced apoptosis, downregulated cell cycle regulatory and transcriptional CDKs and cyclins’ protein expression as well as their activity. Moreover, dual combination of either of these CDK inhibitors with standard chemotherapeutic drugs was found to be synergistic in CRC cells. Thus, we demonstrate that multiple CDK inhibition offers promising therapeutic strategy against CRC.